Datos sobre la dinámica de la flora fanerogámica del Valle de México, con énfasis en especies nativas raras, en peligro de extinción y aparentemente extintas - Rzedowski, Jerzy; Calderón de Rzedowski, Graciela (Instituto de Ecología, A.C., 1993)
A recently concluded inventory reveáis that 68 species of wild flowering plants registered in the past century or in the first half  of íhe present one as members of the native flora of the  Valley of México, do not seem to exist any more in the area. Five of these species (Acourtia matudae, Andropogon schaffneri, Cirsium lomatolepis, Lactuca brachyrrhyncha and Rubus  cymosus) have not been reportad from outside the limits of the  Valley and in consequence may be totally extinct. 620 species of stili extant native flora are evidently scarce or rare in the area, and consequently their permanence is  endangered. Of these, 153 are so vulnerable, that their survival  in next 50 years is not probable, if the present trend of  modification of the environment is maintained.161 species introduced from overseas were found growing as wild plants in the Valley of México in recent decades. !t can be estimated that approximately 50 additional species thriving as  weeds are also adventitious, although these plants are native of  other parts of México and/or Mesoamerica. Finally, the existence of elements is reported, which do not behave as  weeds and certainly are not escapes from cultivation, but  immigrated from neighboring areas, due to modifications caused by human activities. Lists are provided for all discussed groups of species.